SOSIALISASI PRODUK CABAI: UPAYA MAHASISWA KKN PMD UNRAM DALAM MENINGKATKAN EKONOMI DAN KETERAMPILAN MASYARAKAT DESA SURALAGA - Gazali, Lalu Idlofi Rosihan; khadariah, Arfidah; Putri, Cinthania Amanda; Putri, Adelia Tamira; Ardiansyah, Lalu Dinar; Gufron, Muhammad; Nurfadliah, Radya; Yulianti, Almira Salsabila; Hidayat, Andri; Taqiuddin, Moh. (Jurnal Wicara, 2025)
The KKN PMD program of Mataram University was implemented in Suralaga. This program focused on community empowerment through innovative chili products. Chili was processed into chili oil named Chililaga with economic value. Socialization included theoretical counseling and direct cooking demonstrations together. PKK cadres and BUMDes actively participated in supporting program success. Communities gained practical skills in production and product packaging. Training also provided understanding about effective digital marketing strategies. Environmental aspects were addressed through continuous waste management education. The program encouraged entrepreneurship development within village community members. Community enthusiasm demonstrated strong support for Chililaga innovation. This activity strengthened synergy between academia, village government, and communities. Chililaga is expected to become sustainable national village innovation model.